ANALISIS IMPLEMENTASI KEBIJAKAN JAKARTA SMART CITY BERBASIS QLUE DAN CROP DI SUKU DINAS PERHUBUNGAN JAKARTA TIMUR - Andrian Heriyanto Putra; Indah Wahyu Maesarini (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The development of technology and information has been very rapid. An online-based information system is used to simplify the work to be more effective and efficient. The development of technology and information is also encouraging the government to continue to innovate, the government began to apply online-based information systems that facilitate communication with the society, this system is known as E-Government. Therefore, the researcher considers it is important to conduct the research An Analysis of Policy Implementation Jakarta Smart City Based on Qlue and Crop in East Jakarta Transportation Sub-Department of Transportation. The problem formultion in this research is how is the implementation of Jakarta Smart City based on Qlue and Crop application in East Jakarta Sub-dept. From that problem formulation, so this study aims to find out the implementation of Jakarta Smart City based on Qlue and Crop application in East Jakarta Sub-Departement of Transportation. The method used by the researcher is descriptive qualitative. Data collection techniques through interviews to informant. The result of this research is a description of the implementation of Jakarta Smart City policy based on Qlue and Crop in East Jakarta Sub-Department of Transportation based on the theory of Edward involving 4 things namely bureaucratic structure, resources, disposition, and communication. From the results of research that the implementation of E-Government in East Jakarta Sub-Departement of Transportation is easy for the public also Transportation Departement about the problems faced by the society. And during the observation, the implementation of E-Government is already running quite well. But there are also suggestions that the researcher proposes the provision of rewards and the addition of Unit Qlue personnel to improve the implementation of Jakarta Smart City based on Qlue and Crop policy will be so much better.